Immune-related genes are differentially associated with negative symptoms subdomains in patients with schizophrenia - V. Golimbet; T. Lezheiko; G. Korovaitseva; N. Kolesina; V. Plakunova; V. Mikhailova (European Psychiatry, 2022)
Introduction Negative symptoms (NS) are a core feature of schizophrenia. NS show heterogeneity proven by factor analysis, which revealed two distinct negative symptoms subdomains: diminished expression (DE) and avolition/apathy (AA) (Marder et al. 2017, Fleischhacker et al. 2019). Some studies showed the different effects of these subdomains on clinical features of schizophrenia that suggest different pathophysiological mechanisms for their development (Stanculete 2021). It has been also shown that the levels of peripheral interleukins (IL) specifically correlate with NS (Enache et al. 2021), in particular, increased IL levels were determined in patients with deficit syndrome compared to non-deficit schizophrenia (Goldsmith et al. 2018).